2015
DOI: 10.1002/smi.2648
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Inflammation and Pain: A Potential Role for Monocytes in Fibromyalgia-related Symptom Severity

Abstract: The possibility that immunological changes might contribute to symptom severity in fibromyalgia (FM) prompted this proof-of-concept study to determine whether differences in monocyte subpopulations might be present in persons with FM compared with healthy controls. Relationships were assessed by comparing specific symptoms in those with FM (n = 20) and patterns of monocyte subpopulations with healthy age-matched and gender-matched controls (n = 20). Within the same time frame, all participants provided a blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…The stress hormones that were released affect virtually all cells and tissues in their bodies, giving rise to the symptoms the participants experienced. However, given that some people can generate and experience psychological stress in the absence of external stressors, the resulting physiological stress response can have the same deleterious effects, including significant effects on immune cell distribution and function (described in Taylor et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress hormones that were released affect virtually all cells and tissues in their bodies, giving rise to the symptoms the participants experienced. However, given that some people can generate and experience psychological stress in the absence of external stressors, the resulting physiological stress response can have the same deleterious effects, including significant effects on immune cell distribution and function (described in Taylor et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Although the authors collected data for both the quantitative and qualitative arms of the study during the same study visit, the data were analyzed and published separately. One component of quantitative data (reported in Taylor et al, 2015) was the Fibromyalgia Impact Questionnaire (FIQ) scores that are included here to provide the reader a gauge of impairment of the participants’ functional status and their perceived health-related quality of life (Bennett, 2005; Burckhardt, Clark, & Bennett, 1991). …”
Section: Methodsmentioning
confidence: 99%
“… 18 A recent study included twenty FM patients and showed that there is a significant role of the monocytes in mediating the pain. 2 The platelet activity is increased in FM indicating there is activity of inflammation, and the patients are at risk of coronary artery disease. The results of this study are in agreement with Haliloğlu 6 who found significant high mean platelet volume and suggested that the patients are at risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size = 1 + 2C (Standard deviation/difference between means) 2 , where C represents the Constant value that derived from the statistical tables and it equals to 7.85 when the 1-β =0.8 and α=0.05. Because fibromyalgia is more common in women than men.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation